2008
DOI: 10.1016/j.neuroimage.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Preictal short-term plasticity induced by intracerebral 1 Hz stimulation

Abstract: Short-term changes of intrinsic properties of neural networks play a critical role in brain dynamics. In that context, epilepsy is a typical pathology where the fast transition between interictal and ictal states is probably associated to intrinsic modifications of underlying networks. In this study, we focused on the correlates of plastic neural mechanisms in the intracerebral electroencephalogram (iEEG). Data were obtained during 1 Hz electrical stimulation in twenty patients suffering from temporal lobe epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…This takes advantage of the excellent temporal and spatial resolution of intracranial EEG. Our data represent the first direct comparison of CCEP responses between clinically-verified early and late sites of seizure propagation; this extends theoretical work suggesting the seizure networks exhibit dynamic changes during ictal spread David et al (2008). sEEG differs significantly from standard subdural grid implantation in terms of the analysis of CCEP data.…”
Section: Discussionsupporting
confidence: 74%
“…This takes advantage of the excellent temporal and spatial resolution of intracranial EEG. Our data represent the first direct comparison of CCEP responses between clinically-verified early and late sites of seizure propagation; this extends theoretical work suggesting the seizure networks exhibit dynamic changes during ictal spread David et al (2008). sEEG differs significantly from standard subdural grid implantation in terms of the analysis of CCEP data.…”
Section: Discussionsupporting
confidence: 74%
“…However, some biophysiological and neurovascular processes are neglected in the current DCM implementation, probably because they may not be easily identified from fMRI data . Nevertheless, DCM has been validated by simulation and experimental studies in humans and animals (David et al, 2008a(David et al, , 2008bMoran et al, 2008). Importantly, the studies of David et al (2008ab) provide evidence for the validity of DCM for inferring network structure from fMRI data using simultaneous fMRI and electroencephalography (EEG) measurements in rodents with epileptic seizures.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Bayesian model comparison suggested that seizure onset could be modelled in terms of changes in intrinsic connectivity (as opposed to extrinsic connectivity). Furthermore, DCM identified fluctuations in synaptic efficacy in the ictal zone; suggesting that the mesial temporal lobe epilepsy studied by David et al (2008) could be explained in terms of a pre-ictal increase in sensitivity to hippocampal afferents from the temporal pole.…”
Section: Dynamic Causal Modelling Of Seizure Dynamicsmentioning
confidence: 94%
“…For example, David et al (2008) analysed seizure activity elicited during electrical stimulation. Bayesian model comparison suggested that seizure onset could be modelled in terms of changes in intrinsic connectivity (as opposed to extrinsic connectivity).…”
Section: Dynamic Causal Modelling Of Seizure Dynamicsmentioning
confidence: 99%